Fascism's Urban Epicenter : Remaking Rome in the Era of Charismatic Politics - Scott, John Beldon (Brill Studies in Architectural and Urban History, 2026)
This book re-imagines the heart of Rome, animating it with the mass rituals of Mussolini's pioneering regime of twentieth-century totalitarianism. It retrieves from a post-war amnesia the ceremonial events, urban sites, and historic monuments of the Duce's charismatic rulership, demonstrating how architecture and urbanism functioned as instruments of persuasion in fashioning a fevered national identity. Piazza Venezia and its surrounding structures emerge anew as material and spatial exemplars of an illiberal modernity, first as incubator and then as cockpit of a novel form of politics. Here you will experience the frenzied crowd at pavement level as a quintessential phenomenon of Fascist rule.